„Świeża woda zdrowia doda”. Opowieść o wodzie. Studium etnograficzne - Plucińska, Aldona Jadwiga (Biuletyn Uniejowski, 2012)
When we consider water in the cultural context, it allows us to understand and appreciate its role and importance in the life of people in the present-day civilisation. It is the main element of many family and annual rituals. It pervades the material, social and spiritual aspects of culture with the same intensity in the 21st century as in the past. Water allows man to move from one space to another and to transgress boundaries without negative consequences for himself and for the environment in which exists. In the past our ancestors used water to propitiate Nature, making also use of their bodies for that purpose, thus creating cultural codes which form cultural sequences connecting the past with the present. The inscription on kitchen towels „Fresh water will make you healthy”, no longer known to the youngest generations in the visual form, still remains actual. Each of us likes fresh water for drinking; we also seek water for its therapeutic properties, and prefer recreation in places with water reservoirs, both natural and artificial. In this way we get closer to the Beginning.